2022
DOI: 10.1055/a-1981-5944
|View full text |Cite
|
Sign up to set email alerts
|

Physiomimetic In Vitro Human Models for Viral Infection in the Liver

Abstract: Viral hepatitis is a leading cause of liver morbidity and mortality globally. The mechanisms underlying acute infection and clearance, versus the development of chronic infection, are poorly understood. In vitro models of viral hepatitis circumvent the high costs and ethical considerations of animal models, which also translate poorly to studying the human-specific hepatitis viruses. However, significant challenges are associated with modeling long-term infection in vitro. Differentiated hepatocytes are best a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 193 publications
(432 reference statements)
0
2
0
Order By: Relevance
“…Due to species differences in animal and human biology, it is highly desirable to develop a robust, available and humanized organ model that reflects human pathological features with viral infection. Organ chips present a rapid and effective tool to explore viral infection and transmission dynamics in a realistic manner 257 , 260 , 263 , 264 . Morphological analysis of respiratory syncytial virus-infected airway organoids uncovered a wide range of impairments ranging from cytoskeletal rearrangements and apical extrusion of infected cells, to syncytia formation 265 .…”
Section: Progress Of Orgocs In Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to species differences in animal and human biology, it is highly desirable to develop a robust, available and humanized organ model that reflects human pathological features with viral infection. Organ chips present a rapid and effective tool to explore viral infection and transmission dynamics in a realistic manner 257 , 260 , 263 , 264 . Morphological analysis of respiratory syncytial virus-infected airway organoids uncovered a wide range of impairments ranging from cytoskeletal rearrangements and apical extrusion of infected cells, to syncytia formation 265 .…”
Section: Progress Of Orgocs In Biomedical Applicationsmentioning
confidence: 99%
“…Both clinical and animal findings showed that viral infection can cause a variety of diseases [257][258][259][260][261]. For example, human immunodeficiency virus (HIV) infection can result in long-term neuropsychiatric adverse effects (neurotoxicity, depression, anxiety, and mood disorders) on individuals [26,83,260,262].…”
Section: Viral Infectionmentioning
confidence: 99%
“…The rapid spread, transmission, and evolution of SARS-CoV2 have increased the risks of pandemics [ 27 , 113 , 114 ]. Developing effective antiviral drugs and vaccines has become increasingly complex with the emergence of new viral strains.…”
Section: Emerging Lung Chips For Sars-cov2 Study During Covid-19mentioning
confidence: 99%
“…Apart from lung chips, liver chips, gut chips, and blood-brain barrier chips have recently been developed independently for SARS-CoV2 research. These diverse microfluidic systems provide a platform for accurate and efficient modeling and preclinical testing, which could ultimately expedite the discovery of effective treatments to combat pandemics [ 114 , 116 , 120 , 138 ]. Another way to address the limitations of microfluidic lung chips is to include multi-organ systems in the design, presenting complicated and near-physiological organ models for host-virus interplay in vitro .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%